Thrombus aspiration in patients with large anterior myocardial infarction - Calais, Fredrik; Lagerqvist, Bo; Leppert, Jerzy; James, Stefan K.; Fröbert, Ole (The American heart journal, 2016)
The TASTE trial did not demonstrate clinical benefit of thrombus aspiration (TA). High-risk patients might benefit from TA. The TASTE trial was a multicenter, randomized, controlled, open-label trial obtaining end points from national registries. Patients (n = 7,244) with ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI) were randomly assigned 1:1 to TA and PCI or to PCI alone. We assessed the 1-year clinical effect of TA in a subgroup with potentially large anterior STEMI: mid or proximal left anterior descending coronary artery infarct lesion, thrombolysis in myocardial infarction 0 to 2 flow, and symptom onset to PCI time ≤5 hours. In this substudy, patient eligibility criteria corresponded to that of the INFUSE-AMI study. In total, 1,826 patients fulfilled inclusion criteria. All-cause mortality at 1 year of patients randomized to TA did not differ from those randomized to PCI only (hazard ratio [HR] 1.05, 95% CI 0.74-1.49, P = .77). Rates of rehospitalization for myocardial infarction, heart failure, and stent thrombosis did not differ between groups (HR 0.87, 95% CI 0.51-1.46, P = .59; HR 1.10 95% CI 0.77-1.58, P = .58; and HR 0.75, 95% CI 0.30-1.86, P = .53, respectively). This was also the case for the combined end point of all-cause mortality and rehospitalization for myocardial infarction, heart failure, or stent thrombosis (HR 1.00, 95% CI 0.79-1.26, P = .99). In patients with STEMI and large area of myocardium at risk, TA did not affect outcome within 1 year.